Selected psychometric properties of the activity participation outcome measure to describe trends in a forensic population of mental health care users - Brooke, Cassandra Ann (My University, 2015)
Minimal research on occupational therapy in forensic psychiatry is available. An outcome measure known as the Activity Participation Outcome Measure (APOM) was developed, yet it had not been applied specifically to Mental Health Care Users (MHCUs) with a criminal offence. Therefore, research on this topic was conducted at a South African forensic psychiatric institution. The aims of the study were to establish selected psychometric properties of the APOM and describe the trends in activity participation in a forensic population. Quantitative methods were employed with a sample size of 62 participating MHCUs for the most part of the study. The tool was found to be stable and suitable for use with forensic MHCUs. Institutionalisation seems to remain a problem in this population, accounting for there being no overall change noted in MHCUs’ level of activity participation. A transitional phase of the explorative level of action was the general level that was maintained by the MHCUs.
A research report submitted to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg, 2015